Choirboys and Choirgirls in the Victorian Church of England - Hillsman, Walter (Studies in church history, 1994)
Although the roles played by children in recent centuries in English church music have varied enormously, it is probably fair to say that choirs with at least some boys’ or girls’ voices have proven more important in musical, ecclesiastical, and social developments than those with none. The most obvious example of this is the choir of men and boys, which has constituted a conspicuous feature of cathedral and some collegiate music since the Middle Ages, except, of course, during the Commonwealth. As women and girls have until very recently been regarded as inappropriate in such music, it is difficult to imagine that the breadth of achievement in musical composition and performance standards associated with these choirs would have been possible if they had contained only men and no boys.